CSR committees and their effect on green practices - Vuong, Ngoc (Economics and Business Review, 2024)
This paper explores the relationship between the presence of corporate social responsibility (CSR) committees and the implementation of corporate green practices. Using data from 445 non-financial Japanese firms from 2010 to 2021, we find a positive impact of such sustainability committees on both integrated and three individual aspects of green initiatives, including internal pollution prevention, green supply chain management, and green product innovation. In addition, our evidence demonstrates a variation in the CSR committees—green practices nexus across diverse groups of firms, based on their exposures to environmental risks. Finally, we claim that CSR-linked compensation and CSR strategy can explain how CSR committees affect firms’ eco-friendly practices. Generally, our study confirms the crucial role of a governance mechanism—CSR committees—that business organisations and policymakers can exploit to promote sustainable behaviours.